42*x+50=26*x+76

Simple and best practice solution for 42*x+50=26*x+76 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 42*x+50=26*x+76 equation:


Simplifying
42x + 50 = 26x + 76

Reorder the terms:
50 + 42x = 26x + 76

Reorder the terms:
50 + 42x = 76 + 26x

Solving
50 + 42x = 76 + 26x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-26x' to each side of the equation.
50 + 42x + -26x = 76 + 26x + -26x

Combine like terms: 42x + -26x = 16x
50 + 16x = 76 + 26x + -26x

Combine like terms: 26x + -26x = 0
50 + 16x = 76 + 0
50 + 16x = 76

Add '-50' to each side of the equation.
50 + -50 + 16x = 76 + -50

Combine like terms: 50 + -50 = 0
0 + 16x = 76 + -50
16x = 76 + -50

Combine like terms: 76 + -50 = 26
16x = 26

Divide each side by '16'.
x = 1.625

Simplifying
x = 1.625

See similar equations:

| (u+4)*10=90 | | 5x-35x^2=0 | | (q-6)*6=12 | | x^2+3xy-4y^2-12+x=0 | | tanx=31 | | 256x^2+81x^2=22 | | 7x+20=3x-4 | | 100y+500=1000-200y | | 2y^2-4y=o | | 1/5x-2=2 | | 256x^2+81x^2=25 | | -33=3(6+x) | | 4(5-x)=28 | | 256x^2+81x^2=5 | | 6x^5+9x^3-4x^2-6=0 | | X^2-10n-25=0 | | 114q=-1176-16q | | 16x^2+9x^2=5 | | x^2+21x-184=0 | | 28+9=34 | | -5(-4)(2)= | | 24q+18=24 | | 33=18q+27 | | 22-6q=19 | | 10x+3x+y+6z-5x+8y-2z= | | 8/9*1/7 | | 13=16q-1 | | 10-12y=2 | | x^3/x^4=0 | | x^3/x^4 | | x^5-x^2=x | | 7p-4=-8+9 |

Equations solver categories